2002
DOI: 10.1366/000370202760295368
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assay for Cyanogenic Constituents in Plants by Raman Spectroscopy: Content and Distribution of Amygdalin in Bitter Almond (Prunus Amygdalus)

Abstract: The ability of Fourier transform Raman spectroscopy to measure cyanogenic glycoside amygdalin was investigated using a standard addition series in which amygdalin (0–700 nmol/mg) was added to ground sweet almond. As an additional test, the method so developed, and further refined, was used to determine endogenous amygdalin in bitter almonds. Using partial least-squares regression (PLSR), the best correlation between the spectra of the standard addition series and amygdalin content exhibited a value of 0.999, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…However, they are similar to the 290 mg HCN per 100 g of tissue reported by Micklander et al. (12). These data are not meant to suggest that Sample 1 contained 10% bitter almonds, but merely to indicate the ability to confirm their presence.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, they are similar to the 290 mg HCN per 100 g of tissue reported by Micklander et al. (12). These data are not meant to suggest that Sample 1 contained 10% bitter almonds, but merely to indicate the ability to confirm their presence.…”
Section: Resultssupporting
confidence: 91%
“…Micklander et al. (12) report an amygdalin value of 110 nmol/mg in bitter almonds, or 50 mg/g. According to Sánchez‐Pérez et al.…”
Section: Resultsmentioning
confidence: 99%
“…They are accumulated in several plants acting as a defense system against fungi and herbivores. Micklander et al [68] reported a development of a method assessing the content and distribution of cyanogenic glycoside amygdalin in bitter almonds [8,68]. They choose Raman spectroscopy for analysis because the nitrile group gives rise to strong Raman band near 2240 cm À1 whereas in IR spectroscopy this group can be recognized only with low intensity.…”
Section: Nitrile Compoundsmentioning
confidence: 99%
“…As a consequence of significant improvements of micro-Raman spectroscopy technology, an increasing attention has been given to the applications of Raman spectroscopy to heterogeneous systems such as those used in the food industry [2,3]. Raman spectroscopy has been successfully employed in the characterization of starch and pectin in potato [3], bitter almonds [4] and for edible oil authentication [5]. In particular, powdered pectin has been extensively investigated by means of FT-IR and FT-Raman spectroscopy [6].…”
Section: Introductionmentioning
confidence: 99%